Planning impairments in schizophrenia: specificity, task independence and functional relevance - Holt, Daniel; Wolf, Jürgen; Funke, Joachim; Weisbrod, Matthias; Kaiser, Stefan (Schizophrenia research, 2013)
The present study investigated the specificity of planning impairments in schizophrenia compared to unipolar major depression. Multiple measures of planning ability were employed to assess the task independence of a planning deficit. Furthermore, the predictive power of planning ability with regard to functional outcome was analyzed. A total of 80 participants completed a comprehensive neuropsychological assessment with an emphasis on executive functions and planning ability. The sample consisted of 28 patients with schizophrenia, 28 patients with depression and 24 healthy controls. Both patient groups were impaired on measures of attention, working memory and planning, but only planning ability differentiated between patient groups. The deficit was evident across different measures of planning ability and was the best overall predictor of functional outcome. These results provide evidence for the relative specificity of a planning deficit in schizophrenia and show that the deficit is not task-specific but likely affects central cognitive control processes critical for planned behavior. The observed relation to functional outcome supports the clinical relevance of planning ability.
Gesehen am 15.09.2021